On the possibility of changing the trajectory of a projectile or rocket based on aerodynamic impact in the shock wave zone - Zhakatayev, Toksan; Konysbekova, Gulbarshyn (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
A physical hypothesis is proposed that it is possible to change the design trajectory of the projectile on the basis of mechanical action on the entire volume of shockwave zones with a unilateral, asymmetric presence of the second projectile. Deviating from the original trajectory results in a positive result when it comes to a defensive task. A new semi-empirical model has been developed and compiled, which allows you to calculate the trajectory of the projectile taking into account the air resistance to movement. In the new model, it is recommended that only four easily detectable values​ ​ be used in upcoming experiments: the initial departure speed , the maximum altitude , the maximum flight range and the full time. The calculation scheme uses iterative calculations. On the basis of which the values ​ ​ of numerical coefficients in the semi-empirical model are specified. The physical idea that external powerful laser radiation can heat the side surface of the projectile and the entire zone of wave jumps of the seal is justified. On one side of the semi-plant, that is, it is one-way heating. The asymmetrical thermal state on both sides of the missile may cause the missile or projectile to deviate from the previously assigned heading. This circumstance is also in favor of the proposed idea.